2016
DOI: 10.1177/0961463x15587833
|View full text |Cite
|
Sign up to set email alerts
|

Time perspective in adolescents and young adults: Enjoying the present and trusting in a better future

Abstract: Time perspective is crucial in adolescence and youth, when individuals make important decisions related to their present and future. The focus of this research was to use the six-factor short version Zimbardo Time Perspective Inventory (S-ZTPI) scale in a sample of adolescents and young adults, and to analyse its associations with decision-making, relational styles and engagement. A structural equation model of the effects of S-ZTPI on these variables was computed, and its psychometric properties were found ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 41 publications
7
23
0
1
Order By: Relevance
“…In turn, a dependent style was related to higher scores on Past Negative as well as Future Negative, as were scores on the scale reflecting the avoidant style. Similar associations between GDMS dimensions and TP dimensions were observed in a study involving an adolescent/student sample by Molinari et al (2016). Thus, individuals scoring high on the negative temporal frame (Past/Future Negative) may tend to adopt a decision style that is avoidant and dependent.…”
Section: Introductionsupporting
confidence: 66%
“…In turn, a dependent style was related to higher scores on Past Negative as well as Future Negative, as were scores on the scale reflecting the avoidant style. Similar associations between GDMS dimensions and TP dimensions were observed in a study involving an adolescent/student sample by Molinari et al (2016). Thus, individuals scoring high on the negative temporal frame (Past/Future Negative) may tend to adopt a decision style that is avoidant and dependent.…”
Section: Introductionsupporting
confidence: 66%
“…A present-oriented time perspective, on the contrary, constitutes a risk-factor for the development of strategic planning skills, but a promoting factor for expressive competencies, a set of skills that foster long-lasting and intimate relationships, as another research has shown (Holman & Zimbardo, 2009;Molinari, Speltini, Passini, & Carelli, 2015). Both types of competencies are nowadays requested to deal successfully with the challenges posited by post-modern society to the youngest generations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, researchers have found that time attitudes have correlations with adaptive and maladaptive functioning in samples of adolescents. Positive time attitudes have meaningful associations with academic achievement (Adelabu, 2007; Wyman, Cowen, Work, & Kerley, 1993), educational outcomes (Andretta, Worrell, & Mello, 2014), psychological well-being (Andretta et al, 2014; Seginer, 2008; Worrell & Mello, 2009), self-efficacy (McKay, Percy, Cole, Worrell, & Andretta, 2016), career decisions (Ferrari, Nota, & Soresi, 2010), relational styles and engagement (Molinari, Speltini, Passini, & Carelli, 2016), and negative time attitudes have statistically and practically significant positive associations with perceived stress (Andretta et al, 2014), risky behavior (Laghi, Baiocco, D’Alessio, & Gurrieri, 2009; Laghi, Liga, Baumgartner, & Baiocco, 2012), and alcohol use in early adolescence (McKay et al, 2016). Consequently, it is important to be able to measure the time attitudes of adolescents robustly so that these topics may be examined in this age group specifically.…”
Section: Time Attitudes In Adolescencementioning
confidence: 99%